Britain's Butterflies - Newland, D. E. (David Edward); Tomlinson, David; Swash, Andy; Still, Rob (WildGuides., 2015)
Britain's Butterflies is a comprehensive and beautifully designed photographic field guide to the butterflies of Britain and Ireland. Containing hundreds of stunning colour photographs, this revised and updated edition provides the latest information on every species ever recorded. It covers in detail the identification of all 59 butterfly species that breed regularly, as well as four former breeders, 10 rare migrants and one species of unknown status. The easy-to-use format will enable butterfly-watchers--beginners or experts--to identify any species they encounter.